Welcome to the Laparoscopic Surgery! - Levi Sandri, Giovanni Battista (Laparoscopic Surgery, 2017)
Dear friends, In the last years hepatobiliary and pancreatic laparoscopic surgery have made giant steps forward. Many countries launch national and international prospective databases of LS. The first guideline is now available for laparoscopic liver surgery. In the same way, minimally invasive surgery has grown with many options for surgeons.